Population dynamics of the cyprinid fish, Amblypharyngodon mola (Hamilton) from the Kaptai lake, Bangladesh (Chittagong University Journal of Biological Sciences, 2013)
Length frequency based population dynamics of the small indigenous cyprinid fish, Amblypharyngodon mola from the Kaptai lake (an artificial water reservoir), Bangladesh were studied using the computer based FiSAT program. Growth parameters La and K were found to be 104.65 mm and 0.95 year-1 respectively. The annual rate of natural mortality (M), fishing mortality (F) and total mortality (Z) were found to be 1.22, 2.04 and 3.26 respectively. Exploitation rate (E) was 0.63, while maximum yield per-recruit (Emax) was estimated as 0.678. The suitable selection pattern (L50) was found to be 51.09 mm. The yield per recruit and biomass per recruit determined as a function of Lc/La and M/K were estimated as 0.49 and 1.28 respectively. The Wetherall plot provided estimates of La and Z/K were 103.38 mm and 3.31 respectively. Growth performance index (?? = 4.017) was found to be suitable. Virtual population analysis (VPA) showed that the maximum number of A. mola was caught between the total length of 75 to 93 mm with values of F exceeding to 2.04 year-1. The estimated mean biomass was found to be 2.81 metric tons. The fish was recruited in the fishery during March to October with maximum in July. DOI: http://dx.doi.org/10.3329/cujbs.v4i1.13398 The Chittagong Univ. J. B. Sci.,Vol. 4(1&2):141-151, 2009